Biotic interactions between the human pathogen Legionella pneumophila and nematode grazers in cooling tower biofilms. - Christin Ortlieb; Aurélie Labrosse; Liliane Ruess; Michael Steinert (PLoS ONE)
Biofilms in cooling towers represent a common habitat for the human pathogen Legionella pneumophila. Within the biofilm consortium, frequent interactions with protozoa, i.e. amoebae and ciliates, were reported, while nematodes have only recently been considered as potential environmental reservoir for the pathogenic bacteria. This study is the first approach to investigate the biotic interactions between L. pneumophila and bacterial-feeding nematodes in a semi-natural biofilm model. The species were Diploscapter coronatus, Diploscapter pachys, Plectus similis and Plectus sp., which all co-occur with L. pneumophila in the environment. Biofilms derived from cooling towers were either inoculated with mCherry-labeled L. pneumophila solely or in combination with GFP-labeled Escherichia coli. All experiments were conducted in single-species set-ups and multi-species (D. coronatus and P. similis) set-ups, to account for interspecific competition. Bacterial ingestion was assessed after 24 and 96 h as fluorescence patterns in the digestive tract of the nematodes using confocal laser scanning microscopy. L. pneumophila cells were ingested by all nematode species, with D. coronatus having the highest pathogen load. The fluorescence intensity (i.e. bacterial load) varied between compartments within the digestive tract and was independent of incubation time. Bacterial cells accumulated mostly around the cardia and in the intestine, while less cells were found within stoma and pharynx. Interspecific competition changed the pattern, i.e. with incubation of D. coronatus and P. similis in the same biofilm a significantly higher pathogen load occurred in the intestine of D. coronatus than P. similis after 24 h and 96 h. Remarkably, when given a choice between L. pneumophila and E. coli, P. similis was the only nematode species containing both bacteria after incubation for 24 h. None of the other nematode species contained E. coli after 24 h and 96 h incubation, while L. pneumophila was present. This study thus provides the first evidence, that under environmental conditions L. pneumophila is a frequent diet of bacterial-feeding nematodes, highlighting their potential as pathogen vectors or even host in cooling tower habitats.